Tinjauan Zakat, Infak, dan Sedekah sebagai Bentuk Transfer Kekayaan: A Review of Zakat, Infaq, and Sadaqah as Forms of Wealth Transfer - Achmat Subekan; Azwar Azwar (Program Studi Akuntansi Lembaga Keuangan Syariah, Politeknik Wahdah Islamiyah Makassar, 2025)
This study aims to describe the concept of zakat, infak, and sadaqah (ZIS) from the perspective of Islamic economics as instruments of wealth transfer and to explain their roles in creating a just and sustainable distribution of wealth within society. The research employs a qualitative approach using the library research method. Data analysis is conducted descriptively and analytically through normative-theological and structural-economic approaches, in order to reveal both the spiritual values and economic functions of ZIS in the context of wealth redistribution. The findings indicate that zakat, infak, and sadaqah play a strategic role in maintaining the socio-economic balance of society. These instruments function as effective mechanisms of wealth transfer that help reduce disparities between the rich and the poor. Beyond being an act of obedience to Allah, ZIS also strengthens social solidarity, promotes economic self-reliance, and realizes falah—the attainment of well-being in this world and the hereafter. Therefore, ZIS represents an Islamic economic instrument that is not only spiritually oriented but also makes a tangible contribution to equitable economic development and social sustainability.